Unusual presentation of Thornwaldt cyst in the elderly: a case report - Jacob, Betty Mariam; Jayaram, Shilpa Muddan; B. V., Manjula; Rajagopal, Pradhepa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Thornwaldt cyst is an uncommon developmental midline cystic lesion arising from the pharyngeal bursa. It is most frequently detected in younger patients incidentally during imaging or diagnostic nasal endoscopy (DNE), and may later in the course of the disease present with symptoms secondary to nasal obstruction. A 75-year-old male presented with symptoms of progressive persistent nasal obstruction since three years, that worsened over past four months. DNE and Contrast enhanced computed tomography (CECT) showed a large midline nasopharyngeal cystic mass fully occupying the choana, measuring ~3×2 cm. Patient underwent transnasal endoscopic coblation-assisted excision of cyst where cheesy material and thick mucoid cyst content was identified. Histopathology showed Cyst wall lined by respiratory epithelium with reactive lymphoid cells. Follow up at 1 week and 2 months showed good postoperative healing of nasopharynx with no evidence of recurrence. Although rarely seen at this age, Thornwaldt cyst can be considered as a potential diagnosis in elderly patients presenting with nasopharyngeal mass- like lesion. In our experience with this case transnasal endoscopic coblation- assisted excision is an effective method for removal of nasopharyngeal cyst like lesions by providing adequate visualisation and access, with coblation wand acting as a single tool for excision, content aspiration and hemostasis.